Tuberculosis outbreak among high school students in Novi Pazar, Serbia 2016: a retrospective-cohort study - Maja B Stosic; Dragana Plavsa; Nikoletta Mavroeidi; Dragana Jovanovic; Violeta Vucinic; Goran Stevanovic; Lidija Sagic; Sefadil Spahic; Uros Rakic; Anita Grgurevic (Journal of Infection in Developing Countries)
Introduction: Between February and November 2016, 17 tuberculosis (TB) cases were identified among high school students in Novi Pazar, Serbia. The objectives of our study were to describe the outbreak, to identify potential risk factors and to evaluate the applied control measures.